Comparison of Bioactive Compound Content in Carica papaya and Manihot esculenta Leaf Extract Based on FTIR (Fourier Transform Infrared) Analysis in Traditional Dengue Hemorrhagic Fever (DHF) Therapy - Sistani Huzainiyah; Elsa Defitri; Funsu Andiarna; Eva Agustina; Risa Purnamasari; Nova Lusiana; Funsu Andirna; Irul Hidayat (International Conference on Sustainable Health Promotion, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus transmitted by Aedes aegypti, often leading to thrombocytopenia. Herbal-based traditional therapies, such as papaya leaves (Carica papaya L.) and cassava leaves (Manihot esculenta Crantz), are considered potential supportive treatments. This study aims to compare the bioactive compounds of both plants through phytochemical screening and Fourier Transform Infrared (FTIR) analysis. The phytochemical results revealed that papaya leaves contain alkaloids, flavonoids, phenolics, tannins, saponins, steroids, and triterpenoids, while cassava leaves contain alkaloids, flavonoids, phenolics, tannins, and triterpenoids. FTIR analysis identified functional groups O–H, C=O, aromatic C=C, C–H, and C–O, indicating the presence of flavonoids, polyphenols, and glycosides. Pharmacologically, papaya leaf extract demonstrated greater potential as it has been clinically proven to increase platelet count through hematopoiesis stimulation and gene regulation. In contrast, cassava leaf extract exhibited antioxidant and hematopoietic potential but with limited clinical evidence. Therefore, papaya leaves are considered more effective as a traditional supportive therapy to aid platelet recovery in DHF patients.